COMMUNITY PARTICIPATION IN AGRO-TOURISM DEVELOPMENT AT KARANGSARI, BLITAR, EAST JAVA - Amanda Putri Nastiti; Prof Luchman Hakim; Soemarno - - (Journal of Environmental Engineering and Sustainable Technology, 2019)
AbstractCommunity participation is one of the keys to success in the process of developing agrotourism in an area. This study aims to analyze the level of community participation in the development of Agro-tourism in Karangsari, Blitar, East Java. Community involvement in the planning, implementation, evaluation, and USE of the results or output is a major factor in developing Karangsari Starfruit Agro-tourism. Data collection research was carried out by distributing questionnaires to respondents consisting of stakeholders and communities around the agrotourism site. The data is processed using Microsoft Excel 2013 and Rank-Spearman Correlation Analysis using IBM SPSS 20. The results of the study show that the lack of community participation in the agrotourism development process occurs because it is influenced by internal factors such as age, education, employment, income level and length of stay. In addition to the influence of these internal factors, community members are also still not involved in any agrotourism development activities. The participation of the community can be improved by conducting activities that require the surrounding community to participate.